2022
DOI: 10.21037/qims-22-218
|View full text |Cite
|
Sign up to set email alerts
|

Morphological changes in the orifices of the left atrial appendage and left atrium in patients with atrial fibrillation

Abstract: Background: As an integral part of the left atrium (LA), the left atrial appendage (LAA) plays an important role in atrial fibrillation (AF). However, the relationship between LAA remodeling and AF has not been clearly defined. This retrospective case-control study aimed to assess the morphological and functional features of the LA and the LAA in AF patients using images obtained by computed tomography angiography (CTA).Methods: A total of 140 AF patients and 64 patients without AF or other cardiovascular dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…It because prolonged AF will cause delayed contraction of left atrial appendage neck. The studies showed [24]the morphologic change of the LAA ori ce in AF patients was more circular than that of the control participants, Therefore, there is little difference in dispersion of peak time in the basal segment of left atrial appendage, which is consistent with our research results. The LAA ori ce major and minor axes, area, and perimeter, and the LAA depth of the female patients were signi cantly greater than those of their male [24].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It because prolonged AF will cause delayed contraction of left atrial appendage neck. The studies showed [24]the morphologic change of the LAA ori ce in AF patients was more circular than that of the control participants, Therefore, there is little difference in dispersion of peak time in the basal segment of left atrial appendage, which is consistent with our research results. The LAA ori ce major and minor axes, area, and perimeter, and the LAA depth of the female patients were signi cantly greater than those of their male [24].…”
Section: Discussionsupporting
confidence: 91%
“…The studies showed [24]the morphologic change of the LAA ori ce in AF patients was more circular than that of the control participants, Therefore, there is little difference in dispersion of peak time in the basal segment of left atrial appendage, which is consistent with our research results. The LAA ori ce major and minor axes, area, and perimeter, and the LAA depth of the female patients were signi cantly greater than those of their male [24]. However, basal segments of the LAA such as left lateral ridge (LLR) and baso-medial appendage segment (BMAS) near the vestibule of the mitral valve are composed of over 4 mm thick myocardial tissue [25,26].…”
Section: Discussionsupporting
confidence: 91%
“…The left atrial volume, measured by CT or magnetic resonance imaging (MRI), is a widely used parameter in studies on AF and is a superior measurement in terms of its accuracy and reproducibility, and prognostic power ( 5 , 14 - 16 ). The current study is consistent with prior research ( 5 , 14 , 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ectopic pacemakers in patients with AF mainly originate in the pulmonary vein, and pulmonary vein isolation is the cornerstone of catheter ablation ( 19 ). Therefore, the risk predictors of postradiofrequency ablation AF recurrence in previous studies were mostly concentrated in the LA, LAA, and pulmonary vein ( 20 , 21 ). Santangeli et al noted that the incidence of extrapulmonary venous triggered lesions in patients with AF was 11%, and the common sites were the crista terminalis, SVC, RAA, and LAA ( 22 ).…”
Section: Discussionmentioning
confidence: 99%